PORTRAYAL OF BALINESE WOMEN IN OKA RUSMINI’S EARTH DANCE: A FEMINIST APPROACH - Setianingtyas, Luh Eka Margarita; Djohan, Rita Sutjiati; Trijanto, Sugeng (Journal of Language and Literature, 2016)
This undergraduate thesis analyzed the Balinese women in Earth Dance by Oka Rusmini. The writer chose this novel because this novel describes the gender inequalities suffered by Balinese women and kinds of Balinese women resistance against gender inequalities by feminist approach, which in this undergraduate thesis the elaboration of the approach employed radical feminist that is radical feminist. The writer uses descriptive qualitative method. Collecting data in this research is done by reading some books, reading some journals, and searching information on the internet. The aims of the research are to describe the kinds of gender inequality against Balinese women and to describe the kinds of Balinese women resistance against gender inequalities in the novel Earth Dance by Oka Rusmini. The results of the research are; first, violence, unfaithful, stereotype, and double burden are the kinds of gender inequality experienced by the Balinese women; and second, celibacy, lesbian, and resist the custom are the kinds of Balinese women resistance against gender inequalities in Earth Dance by Oka Rusmini.Keywords: Feminism, Radical Feminist, inequality, resistance, Balinese women, Earth Dance.